2011
DOI: 10.1371/journal.pone.0022971
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vaccine Coverage within Social Networks in Cholera Vaccine Efficacy

Abstract: BackgroundTraditional vaccine trial methods have an underlying assumption that the effect of a vaccine is the same throughout the trial area. There are, however, many spatial and behavioral factors that alter the rates of contact among infectious and susceptible individuals and result in different efficacies across a population. We reanalyzed data from a field trial in Bangladesh to ascertain whether there is evidence of indirect protection from cholera vaccines when vaccination rates are high in an individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The Matlab cholera vaccine trial analysis presented in this paper extends previous association-type analyses of population-level vaccine efficacy (Ali et al 2005, 2009; Root et al 2011) to inference about the different causal effects of the vaccine(s). Such inference quantifies the expected number of cholera cases prevented for different levels of vaccine coverage in both vaccinated and unvaccinated individuals, providing clearer interpretation of and additional insight into the population-level impact of vaccination for investigators and policy makers.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The Matlab cholera vaccine trial analysis presented in this paper extends previous association-type analyses of population-level vaccine efficacy (Ali et al 2005, 2009; Root et al 2011) to inference about the different causal effects of the vaccine(s). Such inference quantifies the expected number of cholera cases prevented for different levels of vaccine coverage in both vaccinated and unvaccinated individuals, providing clearer interpretation of and additional insight into the population-level impact of vaccination for investigators and policy makers.…”
Section: Discussionmentioning
confidence: 82%
“…These results suggest possible interference between individuals in spatial proximity to one another. Similarly, Root et al (2011) found that incidence of cholera among placebo recipients declined with increasing vaccine coverage within an individual’s kinship network.…”
Section: Introductionmentioning
confidence: 94%
“…Likewise, Root et al . () concluded that the risk of cholera among placebo recipients was inversely associated with level of vaccine coverage in their social networks. Motivated by these association analyses, Perez‐Heydrich et al .…”
Section: Application To Randomized Trial Of Cholera Vaccinementioning
confidence: 99%
“…Following Root et al . (), the third interference structure is defined according to a kinship‐based social network between baris. The Matlab Demographic Surveillance System recorded the exact dates and bari of residence over time for each individual.…”
Section: Application To Randomized Trial Of Cholera Vaccinementioning
confidence: 99%
See 1 more Smart Citation